Penerapan Metode User Centered Design pada Aplikasi UMKM Berbasis Android (Studi Kasus : UMKM Kenyot Susu Boyolali) - Nurlaela, Lusiana; Setiawati, Donna; Wulandari, Fera Tri (JITU, 2024)
MSME Kenyot Susu is one of the MSMEs in Boyolali that sells various processed foods and drinks made from colostrum milk. Currently, product introduction activities only involve participating in events and bazaars so that the community reach is not wide enough. Reseller registration is currently still done manually by coming directly to the location. This research focuses on developing Android-based MSME applications using the User Centered Design method which was built using the PHP, Javascript, and Dart programming languages and using the Flutter framework. The testing method uses a usability test with a questionnaire and is measured using a Likert Scale. This research succeeded in developing an Android application as an MSME information system that displays MSME profiles, products sold, reseller data but does not include buying and selling transactions. From the test results, an average score of 79% was obtained in the category (agree/good/like), which shows that the application design that was built was in accordance with user expectations.